Keunggulan Komparatif Ekspor Kopi di Indonesia - Ramadhana, Ahmad Wildan Saputra; Aulia, Avinda Distaniar; Ulum, Toifur (CV. Kurnia Grup, 2024)
Indonesia has a significant comparative advantage in the coffee export sector, supported by high product quality, diversity of coffee types, and ideal natural conditions for coffee cultivation. The unique taste of coffee in Indonesia, such as Arabica and Robusta, is recognized and appreciated in the international market. Nonetheless, Indonesia's coffee industry faces several challenges such as price fluctuations, climate change, inadequate infrastructure, limited access to funding, and intense global competition. To overcome these challenges and strengthen its position in the global market, a comprehensive strategy is needed. These strategies include improving product quality and consistency, developing infrastructure, diversifying and innovating products, increasing funding, and strengthening marketing and promotion. The implementation of these strategies is expected to improve the welfare of coffee farmers and producers, maximize Indonesia's coffee export potential, and maintain its comparative advantage in the global market. In addition, it is also important to increase collaboration between the government, private sector, and farming community in facing the challenges. With strong synergy, Indonesia's coffee industry can continue to grow and compete in the international market, and contribute significantly to the national economy.